Aspects Influencing Access to HIV/AIDS Services among Afghan Immigrants in Iran: A Qualitative Study - Elham Ghasemi; Fatemeh Rajabi; Reza Majdzadeh; AbouAli Vedadhir; Reza Negarandeh (Shiraz University of Medical Sciences, 2022)
Background: A successful response to the risk of human immunodefficiency virus (HIV) infection among immigrants requires improved access to HIV prevention, diagnosis, and treatment services. However, most immigrants face significant challenges in accessing HIV/AIDS services. The aim of this study was to explore the aspects influencing access to HIV/AIDS services among Afghan immigrants in Iran. Methods: This was a qualitative study using conventional content analysis that was conducted from June 2018 to April 2020 in Tehran, Iran. Purposeful sampling method was performed. We conducted 25 semi-structured interviews with three groups of stakeholders including Afghan immigrants infected with or at risk of HIV (n=8), service providers (n=8), and policymakers/managers/experts (n=9). Inductive qualitative content analysis was applied according to the Granheim and Lundman method. Data were analyzed using Open Code software version 4.03. Results: Aspects influencing access to HIV/AIDS health services were categorized into 3 themes (that were extracted from 9 categories): 1. Cultural aspects (cultural similarities and differences, values and beliefs); 2. Psychosocial aspects (social support, stigma and discrimination); and 3. Service delivery related aspects (awareness, health services coverage and integrity, health services financing, accessibility, and continuity of care). Conclusion: The findings suggest that efforts to improve Afghan immigrants' access to HIV/AIDS health services in Iran need to consider the cultural aspects, increasing HIV awareness, providing support, reducing stigma and discrimination, and improving health services coverage, integrity, financing, and continuity of accessible services.